2018
DOI: 10.1186/s12885-018-4834-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in gonadal impairment in female survivors of childhood cancer: a PanCareLIFE study protocol

Abstract: BackgroundImproved risk stratification, more effective therapy and better supportive care have resulted in survival rates after childhood cancer of around 80% in developed countries. Treatment however can be harsh, and three in every four childhood cancer survivors (CCS) develop at least one late effect, such as gonadal impairment. Gonadal impairment can cause involuntary childlessness, with serious consequences for the well-being of CCS. In addition, early menopause increases the risk of comorbidities such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 39 publications
(30 reference statements)
0
21
0
Order By: Relevance
“…Thus, PanCareLIFE will help to quantify the toll of cancer treatment in relation to specific deficits. Some results were published at virtually the same time as the project ended (e.g., [ 24 , 25 , 26 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, PanCareLIFE will help to quantify the toll of cancer treatment in relation to specific deficits. Some results were published at virtually the same time as the project ended (e.g., [ 24 , 25 , 26 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Detailed methods for DNA collection and genotyping are described elsewhere [27]. For the first aim of the genotype study, a candidate gene approach was applied to validate 10 previously identified single nucleotide polymorphisms (SNPs) associated with hearing loss in childhood cancer patients and survivors [19,28-40]: ACYP2 , LRP2 , NFE2L2 , OTOS , TPMT , SOD2 , SLC22A2 , GSTP1 , ABCC3 , and SLC16A5 [30,32,35,38,40-43].…”
Section: Methodsmentioning
confidence: 99%
“…A stringent quality control protocol was applied where multiple filters were used to ensure the quality of the genetic data prior to either imputations or analysis. The quality control procedure is described elsewhere [27]. To remove poorly genotyped SNPs and individuals from the data, a call rate of 97.5% was applied.…”
Section: Methodsmentioning
confidence: 99%
“…Detailed methods for DNA collection and genotyping are described elsewhere [27]. For the first aim of the genotype study, a candidate gene approach was applied to validate 10 previously identified single nucleotide polymorphisms (SNPs) associated with hearing loss in childhood cancer patients and survivors [19,[28][29][30][31][32][33][34][35][36][37][38][39][40]: ACYP2, LRP2, NFE2L2, OTOS, TPMT, SOD2, SLC22A2, GSTP1, ABCC3, and SLC16A5 [30,32,35,38,[40][41][42][43].…”
Section: Dna Collection and Genotypingmentioning
confidence: 99%